A nickel and cobalt bimetal organic framework with high capacity as an anode material for lithium-ion batteries. Issue 11 (2nd October 2020) - Zheng, Wen; Bi, Wanying; Gao, Xuenong; Zhang, Zhengguo; Yuan, Wenhui; Li, Li
Abstract : The Ni–Co-BTC anode shows excellent electrochemical performance, which could be ascribed to the intercalation/deintercalation mechanism and the synergistic effect of two cations. Abstract : Owing to the high controllability and regular pore structure, metal–organic frameworks (MOFs) have been considered as promising electrode materials. In this work, we report the synthesis of a nickel and cobalt 1, 3, 5-benzenetricarboxylate bimetal organic framework (Ni–Co-BTC) using a common solvothermal method, and investigate its electrochemical performance as an anode material for lithium-ion batteries. The Ni–Co-BTC anode shows a high specific capacity of 1242 mA h g −1 at a current density of 200 mA g −1 in the potential window of 0.01–3.0 V versus Li/Li + along with excellent rate performance (384 mA h g −1 at a current density of 4 A g −1 ), which could be ascribed to the conjugated carboxylates with a stronger π–π interaction and the synergistic effect of two cations. In addition, the mechanism of Li storage demonstrated that Li + inserts into (or extracts from) the carboxylate groups and the benzene ring without the direct engagement of metal ions during galvanostatic charge–discharge measurements. More importantly, the Ni–Co-BTC MOF will be regarded as one of the promising anode materials for advanced Li storage.